A Class IIb Bacteriocin Plantaricin NC8 Modulates Gut Microbiota of Different Enterotypes in vitro - Pu, Jiaqian; Hang, Shuting; Liu, Manman; Chen, Ziqi; Xiong, Jiayi; Li, Yongquan; Wu, Hongchen; Zhao, Xiaodan; Liu, Shuxun; Gu, Qing; Li, Ping (Frontiers in Nutrition, 2022)
The gut microbiota is engaged in multiple interactions affecting host health. Bacteriocins showed the ability of impeding the growth of intestinal pathogenic bacteria and modulating gut microbiota in animals. Few studies have also discovered their regulation on human intestinal flora using an in vitro simulated system. However, little is known about their effect on gut microbiota of different enterotypes of human. This work evaluated the modification of the gut microbiota of two enterotypes (ET B and ET P) by the class IIb bacteriocin plantaricin NC8 (PLNC8) by using an in vitro fermentation model of the intestine. Gas chromatography (GC) results revealed that PLNC8 had no influence on the gut microbiota’s production of short-chain fatty acids (SCFAs) in the subjects’ samples. PLNC8 lowered the Shannon index of ET B’ gut microbiota and the Simpson index of ET P’ gut microbiota, according to 16S rDNA sequencing. In ET B, PLNC8 enhanced the abundance of Bacteroides, Bifidobacterium, Megamonas, Escherichia-Shigella, Parabacteroides, and Lactobacillus while decreasing the abundance of Streptococcus. Prevotella_9, Bifidobacterium, Escherichia-Shigella, Mitsuokella, and Collinsella were found more abundant in ET P. The current study adds to our understanding of the impact of PLNC8 on the human gut microbiota and lays the groundwork for future research into PLNC8’s effects on human intestinal disease.